Efficacy of Locally Adapted Dietary Regimen in the Treatment of Nutritional Marasmus: A Randomized Control Trial - Rahman, ME; Qamruzzaman, K; Bhuian, MMR; Karim, MN; Rahman, MM (Bangladesh Medical Journal, 2014)
Food-based strategies are currently in practice to meet the challenges of micronutrient malnutrition in malnourished children. World Health Organization (WHO) proposed a dietary regimen for such therapy. In resource limited country like Bangladesh, it is difficult to implement the WHO protocol properly. Current study aimed at evaluating the locally adapted peanut based Dhaka Medical College Hospital (DMCH) dietary formula in the treatment of nutritional marasmus. The trial was conducted in Dhaka Medical College Hospital (DMCH) from July 2009 to June 2010. Sixty marasmic patients (based on WHO criteria) admitted in the hospital aged 06 to 59 months who meet the inclusion criteria were enrolled. Children with major congenital anomalies, children having feeding difficulty and bi-pedal edema, severe anemia, severe dehydration, TB, congestive heart failure with shock, critically sick child were excluded. Children were allocated with one of the dietary formula (DMCH regimen or WHO regimen) randomly by box of eight randomization protocol. Both groups were managed in two phase's i.e. initial phase and rehabilitation phase. In the initial phase starter formula was used and during the rehabilitation phase catch-up formula was given. Heath and nutritional education for mother and caregiver was given, Non-immunized children were immunized and discharge was given after fulfilling the criteria. Independent t tests were applied to compare outcome of treatment. Child receiving DMCH regimen took on average 3.47 days to return to smile the time was 4.47 in WHO regimen group (P< 0.01). Rate of weight gain was also higher in the group by around 2.66 gm/kg/day. In DMCH group the time taken to achieve target weight was 13.4 days which was around one day more than that of WHO group (14.3 days). Total amount of F-75 was also required less in WHO group. Most importantly daily treatment cost was higher by around 17 BDT per day in WHO regimen group. Neither of the group experienced any serious adverse effect or fatality. Locally made peanut based DMCH protocol is more efficacious than the WHO regimen for treatment of treatment of nutritional marasmus in the age group 6 months to 59 months. DOI: http://dx.doi.org/10.3329/bmj.v41i2.18808 Bangladesh Medical Journal 2012 Vol. 41 No. 2: 45-49